Perancangan Desain UI/UX Website E-Learning Berbasis Learning Management System dengan Metode Design Thinking - Hudha, Miftakhul; Haryono, Kholid (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This research aims to develop a user interface (UI) and user experience (UX) design for a Learning Management System (LMS)-based e-learning platform for the Central Language Improvement (CLI) community at the Islamic University of Indonesia using the Design Thinking method. Following the empathize, define, ideate, prototype, and testing stages, this research involved administrators, mentors, and students in the development process. Data collection was conducted through direct observation and interviews, followed by analysis using user personas and mind mapping. Usability testing results showed good acceptance levels with Maze scores for Admin (75), Mentor (89), and Students (83), and a System Usability Scale (SUS) score of 75.2 indicating an "Acceptable" category with a "Good" rating. This research successfully produced a UI/UX design that meets user needs in supporting the learning process in the CLI UII community, with recommendations for further development on the admin interface and implementation of learning monitoring features.